Temperature Evolution of Cluster Structures in Ethanol. (16th May 2013) - Golub, P.; Doroshenko, I.; Pogorelov, V.; Sablinskas, V.; Balevicius, V.; Ceponkus, J.
Abstract : The dependence of FTIR spectrum of pure ethanol on the temperature was investigated. The measurements were performed for frozen (the minimum temperature −180°C) and liquid ethanol (the maximum temperature 40°C). All changes in IR spectrum of ethanol during gradual warming were detected and analyzed. On the bases of preset observations, the conclusions concerning the evolution of cluster structures in ethanol during transition from solid (frozen) state to liquid state were made.